Determination of individual bile acids in biological fluids by thin-layer chromatography and fluorimetry. Issue 4 (May 1970) - Panveliwalla, D.; Lewis, B.; Wootton, I. D. P.; Tabaqchali, S.
Abstract : A method is described for the separation and determination of individual bile acids in serum and in intestinal contents, employing thin-layer chromatography and fluorimetry. The mean recovery from intestinal juice was 94% and from serum 82%. Normal values for the individual bile acids of serum and examples of clinical applications of the method are given.